Sickness absence at the French National Electric and Gas Company. Issue 2 (February 1987) - Chevalier, A; Luce, D; Blanc, C; Goldberg, M
Abstract : The certified sickness absence of workers in the French National Electric and Gas Company was studied for 12 months and has been described according to the demographic and occupational characteristics of the employees. The results showed that the principal factors affecting absence are sex, job, and salary. The high percentage of absent women was explained by neither the type of occupation nor family status. Respiratory diseases, accidents, and musculoskeletal and psychiatric disorders were the leading diagnostic categories. Indices of severity, duration, and frequency were calculated and compared between groups. The duration of absence increased with the severity of the medical cause of absence and with the patient's age.